(untitled) (Olhar de Professor, 2021)
The aim of this study is to discuss the legal advice 05/2020 drafted by Conselho Nacional de Educação (CNE) and possible confrontations in the field of Childhood Education. The question line was: How does Childhood Education is affected by COVID-19 Pandemic? It justifies by security of rights hardly conquered in the fiel of childhood education, especially due the fact of been educated in collective non-domestic spaces (BRASIL, 2009), and the emerging possibility of remote activities, specifically on distance learning by video class and other virtual resources for the young child, which could exacerbate even more the social inequality. the writing composition is bibliographic sources and the results indicates the need to face this issue by resisting, which doesn’t means to discard the children in this pandemic times, on the contrary, to make proper ways to assist them.